2020
DOI: 10.1186/s13100-020-00227-7
|View full text |Cite
|
Sign up to set email alerts
|

Intruder (DD38E), a recently evolved sibling family of DD34E/Tc1 transposons in animals

Abstract: Background A family of Tc1/mariner transposons with a characteristic DD38E triad of catalytic amino acid residues, named Intruder (IT), was previously discovered in sturgeon genomes, but their evolutionary landscapes remain largely unknown. Results Here, we comprehensively investigated the evolutionary profiles of ITs, and evaluated their cut-and-paste activities in cells. ITs exhibited a narrow taxonomic distribution pattern in the animal kingdom,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 84 publications
1
14
0
Order By: Relevance
“…Then, these transposase sequences were used as a query to search the genomes deposited in the National Center for Biotechnology Information (NCBI) genome project database (https://blast.ncbi.nlm.nih.gov/Blast, accessed on 25 October 2020) using TBLASTN with an E-value of 1e-100. Subsequently, the best hits were extracted with 2-kb flanking sequences, since most ITm families contain TIRs (including untranslated region) less than 2 kb as previous studies reported, such as DD35E/TR [20], DD36E/IC [21], DD38E/IT [22], DD37D/maT [23], DD39D/GT [23]. The presence of TIRs and TSDs was manually screened in the resulting sequences, to identify potential DNA transposons.…”
Section: Transposon Mining and Annotationmentioning
confidence: 99%
See 4 more Smart Citations
“…Then, these transposase sequences were used as a query to search the genomes deposited in the National Center for Biotechnology Information (NCBI) genome project database (https://blast.ncbi.nlm.nih.gov/Blast, accessed on 25 October 2020) using TBLASTN with an E-value of 1e-100. Subsequently, the best hits were extracted with 2-kb flanking sequences, since most ITm families contain TIRs (including untranslated region) less than 2 kb as previous studies reported, such as DD35E/TR [20], DD36E/IC [21], DD38E/IT [22], DD37D/maT [23], DD39D/GT [23]. The presence of TIRs and TSDs was manually screened in the resulting sequences, to identify potential DNA transposons.…”
Section: Transposon Mining and Annotationmentioning
confidence: 99%
“…The MAFFT program was used to perform multiple alignments of DDE domains [36]. Reference transposase sequences were obtained from GenBank and the references of DD35E/TR [20], DD36E/IC [21], DD37E/TRT [27], DD38E/IT [22], Zator and TP36 [32]. Bacterial transposases from insertion sequence 256 (IS256) were chosen as the outgroup.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 3 more Smart Citations